Analysis of Key Genes Responsible for Low Urea Production in Saccharomyces cerevisiae JH301 - Liang, Zhangcheng; Su, Hao; Ren, Xiangyun; Lin, Xiaozi; He, Zhigang; Li, Xiangyou; Zheng, Yan (Frontiers in Microbiology, 2022)
There is a potential safety risk with ethyl carbamate (EC) in Hongqu Huangjiu production; 90% of the EC in rice wine is produced by the reaction of the urea with the alcohol of Saccharomyces cerevisiae. In our previous experiments, we screened and obtained a S. cerevisiae strain JH301 that offered low urea production. However, the key genes responsible for low urea production of strain JH301 remain unclear. Here, the whole genome sequencing of S. cerevisiae strain JH301 was accomplished via a next-generation high-throughput sequencing and long-read sequencing technology. There are six main pathways related to the urea metabolism of strain JH301 based on KEGG pathway mapping. Three species-specific genes are related to the urea metabolism pathways and were found in comparative genome analysis between strains JH301 and S288c during Hongqu Huangjiu production for the first time. Finally, the ARG80 gene was found to be likely a key gene responsible for low urea production of S. cerevisiae strain JH301, as determined by PCR and qRT-PCR check analyses from DNA and RNA levers. In conclusion, the results are useful for a scientific understanding of the mechanism of low urea production by Saccharomyces cerevisiae during Hongqu Huangjiu fermentation. It also is important to control the urea and EC contents in Hongqu Huangjiu production.